Child-Adult differences in the recovery from high-intensity exercise - Falk, B.; Dotan, R. (Exercise and Sport Sciences Reviews, 2006)
Children recover from physical exertion faster than adults, especially, from high-intensity exercise. It is argued that, qualitatively, this is due mainly to dimensional differences but that, predominantly, it is a quantitative difference, stemming from the lower relative power children can generate and from which they need to recover. Children's lesser power capacity is, in turn, likely due to maturation-dependent neuromotor differences.